EVALUASI PROSES PENGOLAHAN DAGING RAJUNGAN PADA PT KML LOBUK KECAMATAN BLUTO KABUPATEN SUMENEP - Eko Adi Sumitro; Imam Hanafi (Journal of Food Technology and Agroindustry, 2019)
One of crab meat preservation process is used pasteurization. Based on the field observation, there is a problem in the crab meat pasteurized at crab harvest season, so that there are some crab meat hoarding in mini plant which cause of imbalance between amount of crab meat peeler and amount of crab meat. It needs good strategy or technique to make the quality of crab meat stay awake. At this process time, the crab meat is kept by using ice for raw state crab meat and ripe state crab meat to waiting the stripping process. The aim of this research is to assess the different storage of crab meat in the raw state and ripe state by using ice in mini plant which affect the quality of crab meat that have produced before pasteurization process in crab meat organoleptic (appearance, smell, taste, and texture), microbiology (content of TPC, Coliform, and E. coli), and chemically (proximate). The result of this research inform organoleptic ally that quality, microbiology, and proximate result of raw state crab meat and ripe state crab meat.